2022
DOI: 10.1186/s12870-022-03718-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-associated metabolomic profiling reveals the critical role of frost tolerance in wheat

Abstract: Background Low temperature is a crucial stress factor of wheat (Triticum aestivum L.) and adversely impacts on plant growth and grain yield. Multi-million tons of grain production are lost annually because crops lack the resistance to survive in winter. Particularlly, winter wheat yields was severely damaged under extreme cold conditions. However, studies about the transcriptional and metabolic mechanisms underlying cold stresses in wheat are limited so far. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 91 publications
5
24
0
Order By: Relevance
“…Vernalization is a physiological process of plants of great interest, not only from a research point of view, but also from industrial and economic ones, due to its close relation with flowering and fruit production. This explains the wide variety of studies dedicated to comprehending the mechanisms driving it, and that go from genetic, physiological and structural approaches of classical biochemistry (Velanis et al 2017;Amasino, 2004), to, in more recent years, study of the whole composition of biomolecules, namely, omics technologies such as transcriptomics and metabolomics (Villacorta-Martin et al 2015;Lv et al 2022;Chen et al 2021). However, the vast majority of these metabolomic studies are performed using MS rather than NMR, even though this technique has previously been proven useful for metabolite profile analysis in diverse application fields, including biomedicine and food industry (Wu et al 2022;Chowdhury et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vernalization is a physiological process of plants of great interest, not only from a research point of view, but also from industrial and economic ones, due to its close relation with flowering and fruit production. This explains the wide variety of studies dedicated to comprehending the mechanisms driving it, and that go from genetic, physiological and structural approaches of classical biochemistry (Velanis et al 2017;Amasino, 2004), to, in more recent years, study of the whole composition of biomolecules, namely, omics technologies such as transcriptomics and metabolomics (Villacorta-Martin et al 2015;Lv et al 2022;Chen et al 2021). However, the vast majority of these metabolomic studies are performed using MS rather than NMR, even though this technique has previously been proven useful for metabolite profile analysis in diverse application fields, including biomedicine and food industry (Wu et al 2022;Chowdhury et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…2017; Amasino, 2004), to, in more recent years, study of the whole composition of biomolecules, namely, omics technologies such as transcriptomics and metabolomics (Villacorta-Martin et al . 2015; Lv et al . 2022; Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic profiling of wheat under FS identified 88 DAMs, including alkaloids, amino acids, and some phenolic acids, with 13 metabolites closely associated with CS tolerance (Lv et al, 2022b).…”
Section: Metabolomicsmentioning
confidence: 99%
“…Metabolomic profiling of wheat under FS identified 88 DAMs, including alkaloids, amino acids, and some phenolic acids, with 13 metabolites closely associated with CS tolerance (Lv et al, 2022b). The dynamics of metabolite accumulation were studied in six wheat genotypes to understand the impact of CS (2°C) and prolonged CS (28 days at 10°C, followed by 2°C to day 49) (Vaitkevičiūtė et al, 2022).…”
Section: Omics‐driven Breeding For Temperature‐smart Plantsmentioning
confidence: 99%
“…The analysis found that there are multiple C-repeat Binding Factor (CBF) gene clusters on Fr-A2 loci (Vágújfalvi et al 2003;Miller et al 2006; Baga et al 2007), which participate in cold acclimation process (Motomura et al 2013). The regulation of cold tolerance in wheat from the vegetative stage to the reproductive stage is mainly controlled by Vrn-1, Vrn-2 and Vrn-3 vernalization genes (Babben et In order to obtain more wheat frost resistance genes, the researchers used low temperature induction to excavate out differential genes and clones them (Lv et al 2022). For example, Liu et al cloned the Wcs19 gene in the freeze-resistant wheat variety Annon 0822 based on the cDNA sequence of the wheat Wcs19 gene and mapped it on the 2B chromosome of wheat (Liu 2016).…”
Section: Introductionmentioning
confidence: 99%